Pendidikan Inklusif untuk Kesetaraan Gender: Strategi Pemberdayaan Perempuan Melalui Kurikulum dan Literasi Digital : Tema: Pendidikan untuk Perempuan - Adytia Feri Fradana; Cut Kumala Sari; Nadia Alfira (Jurnal Pendidikan Dirgantara, 2025)
Gender equality in education is a fundamental pillar for sustainable development and the empowerment of women in the modern era. Although significant progress has been made in improving access to education for women in Indonesia, challenges such as gender stereotypes, early marriage, and the digital divide continue to hinder the full participation of women in education. This article explores various strategies for empowering women through education, including the integration of gender-responsive curricula, enhancement of digital literacy, and strengthening women's roles in STEM fields. Using a descriptive qualitative approach, this article aims to provide in-depth insights into the efforts that can be undertaken to achieve gender equality in education in Indonesia.